2000
DOI: 10.1118/1.1323982
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a model‐based treatment planning system for dose computations in the kilovoltage energy range

Abstract: The ability to determine dose distribution and calculate organ doses from diagnostic x rays has become increasingly important in recent years because of relatively high doses in interventional radiology and cardiology procedures. In an attempt to determine the dose from both diagnostic and orthovoltage x rays, we have used a commercial treatment planning system (Pinnacle, ADAC Laboratories, Milpitas, CA) to calculate the doses in phantoms from kilovoltage x rays. The planning system's capabilities for dose com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 27 publications
(22 reference statements)
1
32
0
Order By: Relevance
“…Unfortunately, low-energy x-ray dose calculation methods are not a part of current radiotherapy treatment planning systems and, therefore, this additional imaging dose can not be included in the calculation of total dose to radiotherapy patients. Attempts have been made to incorporate the imaging dose into total patient dose from diagnostic x rays in treatment planning by Alaei et al 5 Due to the increased photoelectric effect, a kV-CBCT procedure results in doses to bone that are up to a factor of 3-4 higher than those in surrounding soft tissue. 4,6 It has been shown that the model-based ͑e.g., convolution/superposition͒ algorithm is capable of computing dose within phantoms of density equal to or less than that of water and that its limitations introduce inaccuracies for calculations through moderately high atomic number materials such as bone for kV x rays.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, low-energy x-ray dose calculation methods are not a part of current radiotherapy treatment planning systems and, therefore, this additional imaging dose can not be included in the calculation of total dose to radiotherapy patients. Attempts have been made to incorporate the imaging dose into total patient dose from diagnostic x rays in treatment planning by Alaei et al 5 Due to the increased photoelectric effect, a kV-CBCT procedure results in doses to bone that are up to a factor of 3-4 higher than those in surrounding soft tissue. 4,6 It has been shown that the model-based ͑e.g., convolution/superposition͒ algorithm is capable of computing dose within phantoms of density equal to or less than that of water and that its limitations introduce inaccuracies for calculations through moderately high atomic number materials such as bone for kV x rays.…”
Section: Introductionmentioning
confidence: 99%
“…4,6 It has been shown that the model-based ͑e.g., convolution/superposition͒ algorithm is capable of computing dose within phantoms of density equal to or less than that of water and that its limitations introduce inaccuracies for calculations through moderately high atomic number materials such as bone for kV x rays. [5][6][7][8][9] Currently the Monte Carlo technique is the most accurate dose calculation method for x rays in the diagnostic energy range in media where there are large atomic number variations, such as a patient body. However, the lack of availability of the Monte Carlo method in commercial radiation treatment planning ͑RTP͒ systems and its long computation time limits its usage for routine patient organ dose calculations.…”
Section: Introductionmentioning
confidence: 99%
“…Another approach for computing radiation dose from kV imaging procedures involves using a convolution/ superposition-based treatment planning system originally designed for MV energies used in radiation therapy. [21][22][23][24] The idea of this approach is to incorporate precalculated kV, instead of MV, energy deposition kernels into an existing commercial treatment planning system to enable computation of dose deposition in the diagnostic energy range. Although this approach has been shown to have potential for estimating doses from clinical imaging procedures, its ability to predict dose to the lung needs further validation and its major limitation is its inability to predict dose in and near bony structures.…”
Section: Discussionmentioning
confidence: 99%
“…Alaei et al 4 , 5 , 6 explored the possible use of a commercial treatment planning system (TPS) to estimate the dose in the kilovoltage range, including that of kV CBCT. They generated kilovoltage X‐ray energy deposition kernels using Electron Gamma Shower (EGS) 4 SCASPH user code (7) and implemented them in the Pinnacle TPS (Philips Medical Systems, Andover, MA; formerly ADAC Laboratories, Milpitas, CA) in 1999 (4) .…”
Section: Introductionmentioning
confidence: 99%
“…They generated kilovoltage X‐ray energy deposition kernels using Electron Gamma Shower (EGS) 4 SCASPH user code (7) and implemented them in the Pinnacle TPS (Philips Medical Systems, Andover, MA; formerly ADAC Laboratories, Milpitas, CA) in 1999 (4) . They subsequently performed dose calculations for a 120 kV static X‐ray beam by using Pinnacle TPS in 2000 (5) . They found that the TPS calculations were overall within 2% for the materials of atomic number less than and equal to that of water compared to the TLD measurements.…”
Section: Introductionmentioning
confidence: 99%